The Effect of Academic Buoyancy Education on Academic Self-Concept and Engagement in Ninth Grade Male Students - Shirkavand, Naser; Fooladi, Asma; Arabsalari, Zahra; Ashoori, Jamal (International Journal of Education and Cognitive Sciences, 2022)
The importance of academic activities is very high for ninth grade students because of choosing a course and enrolling in 10th grade. Therefore, the aim of this study was determine the effect of academic buoyancy education on academic self-concept and engagement in ninth grade male students. This research in terms of purpose was applied and in terms of implementation method was semi-experimental with a pre-test and post-test with a control group. The research population was the ninth grade male students of Pishva city in the 2022-23 academic years, which 40 people of them were selected with using the available sampling method as a sample and randomly divided into two equal groups. The experimental group received 12 sessions of 70 minutes the academic buoyancy education and the control group remained on the waiting list for training. Data were collected with the questionnaires of academic self-concept (Liu and Wang, 2005) and academic engagement (Reeve and Tseng, 2011) and analyzed by chi-square and multivariate analysis of covariance method in SPSS-19 software. The results showed that there was a significant difference between the experimental and control groups in terms of both variables of academic self-concept and academic engagement. In other words, academic buoyancy education increased self-concept and engagement in ninth grade male students (P